Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.neubiorev.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Gamma band oscillations in the early phase of psychosis: A systematic review

Abstract: Abnormal gamma oscillations, measured by electroencephalography (EEG), have been associated with chronic psychotic disorders, but their prevalence in the early phase of psychosis is less clear. We sought to address this by systematically reviewing the relevant literature. We searched for EEG studies of gamma band oscillations in subjects at high risk for psychosis and in patients with first episode psychosis. The following measures of gamma oscillations were extracted: resting power, evoked power, induced powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 106 publications
3
48
1
Order By: Relevance
“…These neurochemical modulations mainly affect the basal forebrain and mesopontine regions ( Woolf and Butcher, 2011 ). Electrophysiologically, REM sleep dreams and psychotic states are accompanied by strongly attenuated activation and synchronicity in the gamma frequency band ( Voss et al, 2009 ; Gandal et al, 2012 ; McNally and McCarley, 2016 ; Reilly et al, 2018 ), suggestive of reduced conscious awareness and executive ego functions ( Desmedt and Tomberg, 1994 ; Cavinato et al, 2015 ). By contrast, a relative increase in gamma band activity is observed in lucid dreaming ( Voss et al, 2009 , 2014 ), and it would be interesting to explore if similar patterns can be identified in insightful psychoses.…”
Section: Consciousness In Dreams and Psychosismentioning
confidence: 99%
“…These neurochemical modulations mainly affect the basal forebrain and mesopontine regions ( Woolf and Butcher, 2011 ). Electrophysiologically, REM sleep dreams and psychotic states are accompanied by strongly attenuated activation and synchronicity in the gamma frequency band ( Voss et al, 2009 ; Gandal et al, 2012 ; McNally and McCarley, 2016 ; Reilly et al, 2018 ), suggestive of reduced conscious awareness and executive ego functions ( Desmedt and Tomberg, 1994 ; Cavinato et al, 2015 ). By contrast, a relative increase in gamma band activity is observed in lucid dreaming ( Voss et al, 2009 , 2014 ), and it would be interesting to explore if similar patterns can be identified in insightful psychoses.…”
Section: Consciousness In Dreams and Psychosismentioning
confidence: 99%
“…ASSR has been extensively studied before both in Sz and in rodent models. In Sz, the majority of studies have shown a reduction of ASSR power (e.g., (Hong et al, 2004;Kwon et al, 1999;Light et al, 2006;Reilly et al, 2018;Spencer et al, 2009;Thune et al, 2016), although increases are also reported (Hamm et al, 2012;Kim et al, 2019). Deficits are observed as well across the psychosis spectrum (Parker et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the deficit in psychotic patients for modulating neural networks engaged during WM-related processes in an appropriate manner. Many studies have reported similar neurophysiological disturbances in gamma oscillation patterns in first-episode psychosis (FEP) patients (Lett et al 2014;Senkowski and Gallinat 2015;Başar-Eroglu et al 2007;Reilly et al 2018). Moreover, dysfunctional oscillations in magnetoencephalography delta (8-12 Hz) frequency ranges are present during the engagement of different processes of WM in schizophrenia (Ince et al 2009).…”
Section: Introductionmentioning
confidence: 90%
“…In schizophrenia, however, these gamma oscillations suffer a decrease of the intensity of their signal (for review, Reilly et al 2018). This results first from multiple pre-and postsynaptic receptor abnormalities in PVBCs (Lewis et al 2011;Lewis 2012).…”
Section: Introductionmentioning
confidence: 99%